Determination Of Success Strategies For Women Entrepreneurs SWOT-Based - Tri Sinarti; Madziatul Churiyah (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to identify those factors important for women entrepreneur successand to provide an overview for women entrepreneurs about their strengths, weaknesses, opportunities and threats in trying and determining strategies and their implementation to achieve sustainable success. This study used 22 respondents as female business owner that located in Palembang, who are members of the Sriwijaya ladies prenuer community. This research used SWOT Analysis to determine strengths, weaknesses, opportunities and threats to find the right strategy. The results recommend Agresif strategy, Strengths Oppurtunities, meaning that the organization is in prime and steady condition. So that it is truly possible to continue to expand, increase growth and achieve maximum progress/success and sustainable. This established strategy must receive support from the government so that the contribution of these women entrepreneurs to development is more significant.